Eksplorasi Metode Double Exponential Smoothing Pada Peramalan Nilai Tukar USD Terhadap Rupiah - Edy Widodo; Bella Destia; Febi Permata Putri; Riski Pratama Ramadhan (ESTIMASI: Journal of Statistics and Its Application, 2022)
Currency exchange rate is the price of one unit in domestic currency against foreign currencies. Exchange rates change over time depending on the supply and demand for foreign exchange relative to the domestic currency. This study aims to predict changes in the USD exchange rate against the Rupiah in 2021 using the DES method. The use of the DES method in this forecasting takes into account that the data to be used has a trend which is characterized by the tendency of the data to move up and down over a long period of time. The DES method can also determine the trend equation for the second most extensive smoothing data through a smoothing process. This forecasting system captures patterns from past data and then uses it to project future data. The results of forecasting the USD exchange rate against the Rupiah from 2021 to 2022 show that the exchange rate ranges from IDR 14,512 to IDR 14,744 with a MAPE value of 1.93%.